Σχεδιασμός τετραώροφου κτιρίου από οπλισμένο σκυρόδεμα βάσει των ευρωκωδικών - Χαραλάμπους, Ελένη (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας,Τεχνολογικό Πανεπιστήμιο Κύπρου., 2015)
On the current thesis a four-storey reinforced concrete building was designed based on Eurocodes 0, 1, 2 and 8. The above Eurocodes are concerned with the actions on structures, the design of concrete structures and the design of structures for earthquake resistance. The study was performed with calculations by hand and it’s consisted by a practical background and deals with the design of selected members of the structure. The design includes the design of slabs, beams, columns, walls and footings but also includes the necessary limit mode and the ultimate limit state. The required reinforcements and the distances between the bars were carried out. Successively, the 3DR.Strad program was used for the analysis and the design of the building. At the end, a comparison of the results is presented followed by some comments. The calculations by hand were made with the use of the Standard Method of Detailing Structural Concrete prototype.
Keywords: Eurocode 0; Eurocode 1; Eurocode 2; Eurocode 8; Concrete design; Four storey building; 3DR. Strad; Ευρωκώδικας 0; Ευρωκώδικας 1; Ευρωκώδικας 2; Ευρωκώδικας 8; Σχεδιασμός; Οπλισμένο σκυρόδεμα; Τετραώροφο κτίριο